Novel Cerium- and Terbium-Doped Gadolinium Fluoride Nanoparticles as Radiosensitizers with Pronounced Radiocatalytic Activity - Nikita A. Pivovarov; Danil D. Kolmanovich; Nikita N. Chukavin; Irina V. Savintseva; Nelli R. Popova; Alexander E. Shemyakov; Arina D. Filippova; Maria A. Teplonogova; Alexandra V. Yurkovskaya; Ivan. V. Zhukov; Azamat Y. Akkizov; Anton L. Popov (Biomedicines, 2025)
Background: The use of nanoradiosensitizers is a promising strategy for the precision enhancement of tumor tissue damage during radiotherapy. Methods: Here, we propose a novel biocompatible theranostic agent based on gadolinium fluoride doped with cerium and terbium (Gd0.7Ce0.2Tb0.1F3 NPs), which showed pronounced radiocatalytic activity when exposed to photon or proton beam irradiation, as well as remarkable MRI contrast ability. A scheme for the production of biocompatible colloidally stable Gd0.7Ce0.2Tb0.1F3 NPs was developed. Comprehensive physicochemical characterization of these NPs was carried out, including TEM, SEM, XRD, DLS, and EDX analyses, as well as UV–vis spectroscopy and MRI relaxation assays. Results: Cytotoxicity analysis of Gd0.7Ce0.2Tb0.1F3 NPs in vitro and in vivo revealed a high level of biocompatibility. It was shown that Gd0.7Ce0.2Tb0.1F3 NPs effectively accumulate in MCF-7 tumor cells. A study of their radiosensitizing activity demonstrated that the combined effect of Gd0.7Ce0.2Tb0.1F3 NPs and X-ray irradiation leads to a dose-dependent decrease in mitochondrial membrane potential, a sharp increase in the level of intracellular ROS, and the subsequent development of radiation-induced apoptosis. Conclusions: This outstanding radiosensitizing effect is explained by the radiocatalytic generation of reactive oxygen species by the nanoparticles, which goes beyond direct physical dose enhancement. It emphasizes the importance of evaluating the molecular mechanisms underlying the sensitizing effectiveness of potential nanoradiosensitizers before choosing conditions for their testing in in vivo models.